JLAMPRAMG BATIK VISUALIZATION AS A COMMUNICATION OF PEKALONGAN COMMUNITY (International Conference on Social and Islamic Studies, 2022)
Pekalongan is known as the city of batik which has a variety of batik motifs. One of them is the motif that is Jlamprang batik. This batik is popular with geometric motifs such as squares, rhombuses, circles. Batik is a medium of communication for the community through the motifs it displays. This study aims to determine the meaning of the Jlamprang batik motif as a form of communication through the medium of batik cloth. The research method used is qualitative research by collecting data from informants, a humanist and educator guide at the Pekalongan batik museum. The results of this study are that Jlamprang batik is taken from the word Jlamprang which is the name of a Jlamprang tree which is now quite rare in Pekalongan where this tree is close to the tomb of a prominent figure in the spread of Islam on the coast of Java, namely Sheikh Maulana Al Magribi. Along with the introduction of Islamic teachings, the Jlamprang batik motif is more prominent with geometric motifs that are attached to the values of Islamic spiritual teachings such as the claw motif which has a meaning to motivate Pekalongan people to be diligent in earning a fortune, the Jlamprang fruit motif which is round in shape depicts faith. In addition, the Jlamprang batik motif is also interpreted as the consistent nature of the Pekalongan people.